Analisis SWOT dan Desain Business Model Canvas (BMC) at PT Nordic Solusi Indonesia Batam - Intan Sari Manaping; Maryani Septiana (Journal of Applied Business Administration, 2023)
This research aims to determine how the SWOT Analysis and Business Model Canvas results at PT Nordic Solusi Indonesia are designed to design the right strategy. The research approach uses qualitative descriptive methods. The informants from the study used the snowball sampling technique by conducting interviews with three informants. The results of this study are that from the SWOT analysis results, PT Nordic Solusi Indonesia has an advantage in the Value Proposition and Key Partnership elements. Meanwhile, the weakness lies in Customer Segments, Channels, Key Resources, and Key Activities. Opportunities owned by PT Nordic Solusi Indonesia are in the Revenue Streams element. At the same time, the threats are in the Cost structure element. The applied strategy concept broadens the scope of the Customer Segment. Adding new value to the Value Proposition, such as a member system for customers, expanding sales on PT Nordic Solusi Indonesia channels by opening or creating a particular website separate from the headquarter website, developing existing value in Customer Relationship by providing discounts on certain purchases, holding gatherings or seminars and free training, add website creation services, design, and other traffic to increase Revenue Stream, maximize all existing values in Key Activities and Key Resources, add new partners to Key Partnerships and add to the current Cost Structure with additional capital from existing capital and carry out more explicit and more detailed planning regarding the use of funds at PT Nordic Solusi Indonesia to avoid uncontrolled use of funds.